An Analysis of the Characteristics of a Socio-Cultural Instructional Discourse - Harison Mohd Sidek; Tun Nur Afizah Ariff Zainal; Mohd Muzhafar Idrus; Hazleena Baharun (Universiti Sains Islam Malaysia, 2024)
2015 International Conference on Language Education Conference (ILEC’15) Proceeding Palm Seremban, October 7-8, 2015